Narrative Kill or Capture: Unreliable Narration in International Law. (30th October 2015) - WINDSOR, MATTHEW
Abstract: This article evaluates the benefits of a 'turn to narration' in international legal scholarship. It argues that significant attention should be paid to the narrators who employ international law as a vocabulary to further their professional projects. Theories of unreliable narration help map consensus within international law's interpretive community in a manner that is acutely sensitive to point of view and perspective. The article examines the existence and extent of unreliable narration through a case study: the practice of targeted killing by the Obama administration in the United States. The struggle for control of the narrative, by narrators with different professional roles and cognitive frames, is ultimately a struggle for interpretive power, with the resulting ability to 'kill or capture' divergent narrative visions. Unreliable narration offers a critical heuristic for assessing how narratives are generated, sustained, and called into question in international law, while fostering reflexive inquiry about international law as a professional discipline.